Case report: Transient lactate elevation by intravenous insulin infusion therapy for diabetic ketoacidosis in a patient with mitochondrial DNA 3243 A > G mutation: A glycolysis rebooting syndrome? - Ohwada, Wataru; Kouzu, Hidemichi; Sato, Tatsuya; Sazawa, Kahomi; Matsui, Azumi; Nagano, Nobutaka; Koyama, Masayuki; Ogasawara, Noriko; Takada, Akifumi; Yano, Toshiyuki; Furuhashi, Masato (Frontiers in Cardiovascular Medicine, 2023)
Mitochondrial disease, most cases of which are caused by mitochondrial DNA (mtDNA) mutation, is present with multiple phenotypes including diabetes mellitus, sensorineural hearing loss, cardiomyopathy, muscle weakness, renal dysfunction, and encephalopathy, depending on the degree of heteroplasmy. While mitochondria play an important role in intracellular glucose and lactate metabolism in insulin-sensitive tissues such as muscles, appropriate strategies for glycemic control have not yet been established in a patient with mitochondrial disease, which is often complicated by myopathy. Here, we describe the history of a 40-year-old man with mtDNA 3243A>G who had sensorineural hearing loss, cardiomyopathy, muscle wasting, and diabetes mellitus with stage 3 chronic kidney disease. He developed mild diabetic ketoacidosis (DKA) in the process of treatment for poor glycemic control with severe latent hypoglycemia. According to the standard therapy for DKA, he was treated with continuous intravenous insulin infusion therapy, which unexpectedly resulted in an abrupt and transient elevation in blood lactate levels without exacerbation of heart failure and kidney function. Since blood lactate levels are determined by the balance between lactate production and consumption, an abrupt and transient lactate elevation following intravenous insulin injection therapy may reflect not only enhanced glycolysis in insulin-sensitive tissues with mitochondrial dysfunction but also decreased lactate consumption in the sarcopenic skeletal muscle and failing heart. Intravenous insulin infusion therapy in patients with mitochondrial disease may unmask derangements of intracellular glucose metabolism in response to insulin signaling.